Monitoring position of the electron beam in the air - Boriskin, V.N.; Gurin, V.A.; Popenko, V.A.; Repihov, O.A.; Savchenko, A.N; Tatanov, V.I (Вопросы атомной науки и техники, 2004)
A possibility of operative control position of the electron beam with energy up to 30 MeV, pulse current up to 1 A with 3.5 pulse length and operate frequency from 50 to 300 Hz at the exit of two-structure linac has been investigated. The zone of technological objects irradiated by accelerated electrons is created with the magnet system. The irradiated samples are situated in the ambient air of the linac bunker. Special secondary-emission monitor is developed for the operative control of the beam position on the target. The monitor signals are used by the linac control system.